New urban geographies of West Bengal, East India. Issue 1 (1st January 2020) - van Duijne, Robbin Jan; Choithani, Chetan; Pfeffer, Karin
ABSTRACT: This article is part of a larger research project on new urban geographies in India. Between the population censuses of 2001 and 2011, India witnessed a record increase of 2, 532 new Census Towns, small settlements that meet the country's criteria to be considered 'urban'. This steep increase is intricately linked with decreases in agricultural jobs, but we know very little about the spatiality of these urban geographies, alternative local employment, or the nature of the local economies of Census Towns. Based on a tailored geodatabase, our Main Map visualizes the geography of these heretofore uncharted Census Towns in the state of West Bengal. We then draw on reconnaissance fieldwork to zoom in on a cluster of Census Towns in central Bengal where we find evidence of urban growth that appears linked to road infrastructure, what we described in earlier conceptual work as "emergent highway urbanization". The Main Map and reconnaissance fieldwork contribute to a better, albeit early-stage, understanding of the rapidly changing spatiality of contemporary urbanization in this region.